Achieving High‐Performance Photothermal and Photodynamic Effects upon Combining D–A Structure and Nonplanar Conformation. Issue 17 (6th April 2020) - Chen, Jingya; Wen, Kaikai; Chen, Hao; Jiang, Sai; Wu, Xiaoxi; Lv, Lei; Peng, Aidong; Zhang, Shiming; Huang, Hui
Abstract: Various organic nanoagents have been developed for photothermal therapy (PTT) and photodynamic therapy (PDT) under near‐infrared (NIR) irradiation. Among them, small molecule‐based nanoagents are very attractive due to their advantages of well‐defined chemical structures, high purity, good reproducibility, and easy processability. However, only a few small molecule‐based nanoagents have been developed for PDT under NIR irradiation. Moreover, the mechanism of PDT under NIR is still elusive. Herein, a semiconducting small molecule (BTA) with donor–acceptor–donor structure and twisted conformation is developed for PDT/PTT under NIR irradiation. A large π‐conjugated electron‐deficient unit is used as the core to couple with two electron‐donating units, ensuring the strong absorption under 808 nm. Moreover, the donor–acceptor structures and twisted conformation can reduce the energy gap between the singlet and triplet states ( ∆E ST ) to afford effective intersystem crossing, beneficial for reactive oxygen species generation. The mechanism is probed by experimental and theoretical evidence. Moreover, the BTA nanoparticles exhibit excellent biocompatibility and PTT/PDT in vitro performance under NIR irradiation. This provides a strategy for designing highly efficient PDT/PTT molecular materials. Abstract : A small molecule (BTA) with donor–acceptor (D–A) structure and twisted conformation is synthesized and developed as a nanoagent for the photothermal/photodynamic effect. The D–A structure can ensure strong absorption under 808 nm, which is beneficial for the photothermal effect. The twisted conformation can afford effective intersystem crossing to generate reactive oxygen species and photodynamic therapy (PDT). This provides a strategy for designing highly efficient photodynamic/photothermal therapy molecular materials.